Esplorasi website Perpustakaan Universitas Harvard, Universitas Gadjah Mada dan Universitas Telkom - Muhammad Rasyid Ridlo; Robi Yoswan Zain; Yesika Anggreini Br Ginting; Yoandini Saputri (Berkala Ilmu Perpustakaan dan Informasi, 2021)
Introduction. This article evaluates library websites of world class universities in Indonesia from several aspects including features, responsibility, and speed. One library website overseas is explored as a reference: Harvard University. Data Collection Method. This is a literature study exploring features on library websites of Universitas Gadjah Mada (UGM) and Telkom University. Data analysis. The study used Harvard University library website as a reference. The results were presented into tables to discuss library websites of UGM and Telkom University. Results and Discussion. Harvard University library webiste has 21 features except gallery, UGM has 11 features and Telkom University has 12 features similar to Harvard University library webiste. Our result showed that Library website of UGM and Telkom University still need to be improved as required to be a world class university. All three websites has an adjustable display depending on devices in accessing websites. Those three websites were considered as responsive websites. Based on PageSpeed Insight, they showed good performance. Conclusion. Information on the websites are well-managed, informative, efficient, and accessible. Universities in Indonesia may use several overseas university library websites as a reference.